Cognitive functioning in major depression - a summary - Hammar, Åsa; Årdal, Guro (Frontiers in Human Neuroscience, 2009)
The aim of the present paper is to summarize the research during the past decade regarding cognitive functioning in Major Depressive Disorder (MDD). Cognitive impairment in the acute phase of illness has been frequently reported. The findings are shown in different cognitive domains, such as executive functions (EF), attention, memory and psychomotor speed. Fewer reports have investigated cognitive functioning in MDD in longitudinal studies. Some longitudinal reports show that the impairment observed in the acute phase of illness may be long lasting despite symptom reduction and recovery. However, findings regarding cognitive functioning in depression are divergent. Factors that might contribute to the divergent findings, such as depression subtype, severity and comorbidity are discussed. Clinical implications and focus of future research directions is highlighted. .In conclusion, depression is associated with cognitive impairment in the acute phase of illness, and some reports indicate that this impairment might be long lasting despite symptom reduction and recovery.